Development and in vivo evaluation of a SARS-CoV-2 inactivated vaccine using high hydrostatic pressure - Martina Brandolini; Pietro Rocculi; Michele Morbarigazzi; Alessandra Mistral De Pascali; Giorgio Dirani; Silvia Zannoli; Davide Lelli; Antonio Lavazza; Francesca Battioni; Laura Grumiro; Simona Semprini; Massimiliano Guerra; et al. (npj Vaccines)
Abstract Developing low-cost vaccine production strategies is crucial to achieving global health equity and mitigating the spread and impact of disease outbreaks. High hydrostatic pressure (HHP) technology is a widely used technology employed in the food industry for long-term preservation. This project aims at validating HHP as a cost-effective method for the production of highly immunogenic thermal stable whole-virus SARS-CoV-2 vaccines. Structural studies on HHP-inactivated viruses demonstrated pressure-dependent effects, with higher pressures (500–600 MPa) destabilizing viral morphology. Immunogenicity assessments, in animal models, revealed that 500 MPa treatment elicited the most robust humoral and cellular immune responses, outperforming heat inactivation. Additionally, HHP-inactivated viral preparation retained thermostability for 30 days at 4 °C, reducing cold-chain dependencies and enabling vaccine distribution also in low-resource settings. With its rapid, cost-effective, and scalable production process, HHP presents a transformative, equitable solution for global vaccine development, particularly for emerging pathogens.